The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics–such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha–in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires

L’éducation des enfants dans Le Chrysanthème et le sabre - Benedict, Ruth Fulton; Mécréant, Lise (Le Chrysanthème et le sabre, 1995)
Cet essai, écrit à distance, sur commande de l'Office of War Information, par une femme qui n'était jamais allée au Japon et en ignorait la langue, pour servir de manuel aux forces d'occupation américaines, réussit la gageure de demeurer, de l'avis général des Japonais, l'un des grands livres que l'on ait écrit sur eux. Des articles et des ouvrages ont, après lui, été publiés qui réfutent, complètent, approfondissent, réapprécient les interprétations de Ruth Benedict. Ces débats lui ont conféré la place d'une référence classique." Ce livre traite des habitudes qui paraissent naturelles et que nul ne songerait à remettre en cause au Japon. Il traite des situations où tout Japonais peut compter sur la courtoisie et de celles où il se sent honteux, des circonstances où il éprouve de l'embarras, de ce qu'il exige de lui-même." On y parle des règles de hiérarchie, de bienséance, de l'éducation des enfants, de morale sexuelle, de politique économique ...
Section: 355 p. ; 17 cm.
Keywords: 1900-1999; 1990-1999; approches et analyses; asie; cours; discipline; japon; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; thématiques

Thunder in my soul: a Mohawk woman speaks - Monture-Angus, Patricia (Fernwood Publishing, 1995)
"This book contains the reflections of one Mohawk woman and her struggles to find a good place to be in Canadian society. The essays, written in enjoyable and accessible language, document the struggles against oppression that Aboriginal people face, as well as the success and change that have come to Aboriginal communities. It speaks to both the mind and the heart."–Résumé de l'éditeur.
Section: x, 273 pages ; 23 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; mohawk; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques

Of woman born: Motherhood as experience and institution - Rich, Adrienne (Norton, 1995)
Adrienne Rich's influential and landmark investigation concerns both the experience and the institution of motherhood. The experience is her own—as a woman, a poet, a feminist, and a mother—but it is an experience determined by the institution, imposed on all women everywhere. She draws on personal materials, history, research, and literature to create a document of universal importance. Dans Of Woman Born , initialement publié en 1976, la poétesse et féministe influente Adrienne Rich examine les systèmes patriarcaux et les institutions politiques qui définissent la maternité. En explorant sa propre expérience - en tant que femme, poète, féministe et mère - elle trouve que l'acte de materner est à la fois déterminé par et distinct de l'institution de la maternité telle qu'elle est imposée à toutes les femmes partout dans le monde
Première édition: 1976
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; corps; cours; discours dominant; fem1000; maternité; premier cycle; périodes historiques; régions géographiques; santé; systèmes d'oppressions; thématiques; théories féministes; états-unis

Démocratie et représentation - Riot-Sarcey, Michèle (Kimé, 1995)
La représentation politique est aujourd’hui en crise : partout en Europe, la légitimité des représentants est contestée, sans pour autant que la démocratie, en son principe, soit mise en cause. A partir de ce constat, des chercheurs des différentes disciplines ont questionné la représentation dans son actualité politique et dans sa formation historique. L’usage de la représentation, la délégation d’autorité qu’elle suppose, la violence qu’elle engendre, la domination qu’elle implique, la pratique démocratique qu’elle présuppose ont été soumis à examen par les intervenants au colloque organisé par le Centre Culturel de l’Albigeois. Les disfonctionnements et les apories d’une démocratie, longtemps considérés comme une donnée perfectible, se révèlent comme un simple produit des règles d’un système exclusif, qui contribuent largement à tenir à l’écart des pouvoirs et des lieux de représentation politiques les femmes comme la grande majorité d’une population, par ailleurs de plus en plus politisée.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; interdisciplinarité; occident; premier cycle; périodes historiques; représentation politique; science politique; science politique et droit; sciences humaines; théories féministes